Pengembangan Media Pembelajaran Google Sites Mata Pelajaran IPS Kelas VIII - Pangesti, Eny Dwi; Sabariah, Sabariah; Rahayu, Endah Yulia (JKTP: Jurnal Kajian Teknologi Pendidikan, 2025)
This study aims to develop a Google Sites learning media for Social Studies Class VIII on the material of Ocean Exploration, Colonialism, and Imperialism in Indonesia that is suitable for use in learning. The product is a web. The development model used is ADDIE which consist of five interrelated stages, namely Analyze. Design, Development, Implementation, and Evaluation. The instruments used in data collection are questionnaires, namely closed questionnaires and open questionnaires. Data alaysis techniques use qualittive descriptive analysis techniques and quantitative descriptive analysis techniques. This research was conducted at a public junior high school in Surabaya with 100 students as participants. Media, material and design experts as validators in order to validate the web. The results obtained are that the Google Sites learning media for Social Studies Class VIII on the material Ocean Exploration, Colonialism, and Imperialism in Indonesia is suitable for use for learning. Positive responses from learners in individual trials, small groups, and large groups. Abstrak Penelitian ini memiliki tujuan mengembangkan media pembelajaran google sites mata pelajaran IPS Kelas VIII pada materi Penjelajahan Samudera, Kolonialisme, dan Imperialisme di Indonesia yang layak digunakan dalam pembelajaran. Produk berupa web. Model pengembangan yang digunakan yaitu ADDIE yang terdiri dari lima tahap yang saling berkaitan yakni Analyze, Design, Development, Implementation, dan Evaluation. Instrumen yang digunakan dalam pengumpulan data berupa angket yakni angket tertutup dan angket terbuka. Teknik analisis data menggunakan teknik analisis deskriptif kualitaif dan teknik analisis deskriptif kuantitatif. Penelitian ini dilakukan di salah satu SMP Negeri di Surabaya sejumlah 100 siswa sebagai responden. Ahli media, materi dan desain sebagai validator dalam memvalidasi web. Hasil yang diperoleh adalah media pembelajaran google sites Mata Pelajaran IPS Kelas VIII pada materi Penjelajahan Samudera, Kolonialisme, dan Imperialisme di Indonesia layak digunakan untuk pembelajaran. Tanggapan positif dari pebelajar baik uji coba perorangan, kelompok kecil, maupun besar.